Prevalence of Herpes Simplex Virus Type 1 and 2 (HSV-1 and HSV-2) in the Women with Breast Cancer by Multiplex-PCR method - Fatemeh Kaveh; Kumarss Amini; Mojtaba Sadeh (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2018)
Introduction: Breast cancer is a common malignancy and a major cause of death in women. Viruses are considered as one of the risk factors associated with breast cancer. Herpes simplex virus-1 (HSV-1) and HSV-2 are involved in the pathogenesis of cancer. The present study was conducted to determine the frequency of HSV-1 and HSV-2 in the blood samples of patients with breast cancer using multiplex-polymerase chain reaction (M-PCR) technique. methods: This cross-sectional study was conducted on 60 breast cancer patients within 2014-2015. The infection with HSV-1 and HSV-2 was investigated by M-PCR. All data were analyzed using SPSS software (version 18). Results: Out of the 60 blood samples obtained from patients with breast cancer, 6 (10%) and 3 (5%) samples were positive for HSV-1 and HSV-2, respectively. Conclusion: herpes simplex virus, especially HSV-1, can play a role as a cofactor in the incidence of breast cancer, so further studies are recommended in this area.